2014
DOI: 10.1007/s00204-014-1201-2
|View full text |Cite
|
Sign up to set email alerts
|

Classifying the adverse mitogenic mode of action of insulin analogues using a novel mechanism-based genetically engineered human breast cancer cell panel

Abstract: Insulin analogues are widely used in clinical practice. Modifications on the insulin molecular structure can affect the affinity and activation towards two closely related receptor tyrosine kinases: the insulin receptor (INSR) and the insulin-like growth factor 1 receptor (IGF1R). A switch towards higher IGF1R affinity is likely to emphasize mitogenesis rather than glucose metabolism. Relevant well-validated experimental tools to address the insulin analogue activation of either INSR or IGF1R are missing. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 44 publications
4
27
0
1
Order By: Relevance
“…A study (18) used human breast cancer cell line and proposed a mitogenic classifier based on IGF-1 and X10 and found that insulin glargine is the most potent insulin analog. Similar studies (19)(20)(21) concluded the mitogenic potential of insulin glargine through IGF-1 activation. An experimental study (22) on human cells found that insulin glargine has the same affinity for insulin receptors and insulin-like growth factor 1 but insulin glargine is rapidly degraded to its metabolites M1 and M2, thus, reduced mitogenic signaling through the IGF1R.…”
Section: Animals and Experimental Studiessupporting
confidence: 55%
“…A study (18) used human breast cancer cell line and proposed a mitogenic classifier based on IGF-1 and X10 and found that insulin glargine is the most potent insulin analog. Similar studies (19)(20)(21) concluded the mitogenic potential of insulin glargine through IGF-1 activation. An experimental study (22) on human cells found that insulin glargine has the same affinity for insulin receptors and insulin-like growth factor 1 but insulin glargine is rapidly degraded to its metabolites M1 and M2, thus, reduced mitogenic signaling through the IGF1R.…”
Section: Animals and Experimental Studiessupporting
confidence: 55%
“…Since these studies had no data on insulin treatment among women with diabetes and the duration and severity of diabetes might differ between studies, it is hard to explain differences between their results and ours. In vitro studies have shown that the PI3K signaling pathway [36][37][38][39] and the MAPK pathway [36,37] are significantly upregulated after stimulation of insulin analogues compared to human insulin. In mammary gland tumors of mice, expression of IR, IGF1R and p-AKT was significantly higher in insulin or insulin analogues-treated compared to vehicle-treated mice, while expression of p-ERK was only increased among tumors of mice treated with insulin analogues [21].…”
Section: Discussionmentioning
confidence: 99%
“…After centrifugation (10 minutes, 10,000 rpm), supernatant was collected and the protein concentration was determined (BCA TM Protein Assay Kit; Thermo Scientific, Rockford, IL, USA). The Western blotting procedures and all antibodies were identical to [ 8 ]. In addition, antibodies targeting Her2 (Cell Signaling Technology, Danvers, MA, USA), β-actin, GAPDH, ER-α and EGFR, (Santa Cruz Biotechnology, Santa Cruz, CA, USA) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The binding affinity of insulin analogues to both IR and IGF1R and their subsequent activation and overall mitogenic capacity are currently used as part of the risk assessment in terms of carcinogenic potential of newly developed insulin analogues. This in vitro assessment is limited by the variability in the cell lines, culture conditions and proliferation assays that are used [ 8 , 9 ]. Furthermore, kinetic parameters, such as administration, distribution, metabolism and excretion, cannot always be captured in these in vitro models.…”
Section: Introductionmentioning
confidence: 99%